Window of opportunity in rheumatoid arthritis – definitions and supporting evidence: from old to new perspectives - Karim Raza; Leonie E Burgers; Annette H van der Helm - van Mil (RMD Open, 2019)
The therapeutic window of opportunity in rheumatoid arthritis (RA) is often referred to. However, some have questioned whether such a period, in which the disease is more susceptible to disease-modifying treatment, really exists. Observational studies are most frequently referenced as supporting evidence, but results of such studies are subject to confounding. In addition formal consensus on the definition of the term has never been reached. We first reviewed the literature to establish if there is agreement on the concept of the window of opportunity in terms of its time period and the outcomes influenced. Second, a systemic literature search was performed on the evidence of the benefit of early versus delayed treatment as provided by randomised clinical trials. We observed that the concept of the window of opportunity has changed with respect to timing and outcome since its first description 25 years ago. There is an ‘old definition’ pointing to the first 2 years after diagnosis with increased potential for disease-modifying treatment to prevent severe radiographic damage and disability. Strong evidence supports this concept. A ‘new definition’ presumes a therapeutic window in a pre-RA phase in which the biologic processes could be halted and RA development prevented by very early treatment. This definition is not supported by evidence, although is less well studied in trials. Some suggestions for future research in this area are made.